2020
DOI: 10.1007/s10973-020-09305-7
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of gehlenite glass microspheres

Abstract: The glass of gehlenite composition was prepared by flame synthesis in the form of microspheres. The powder precursor was synthesised by standard solid-state reaction method using SiO 2 , Al 2 O 3 and CaCO 3 . The prepared glasses were characterized from the point of view of surface morphology, phase composition and thermal properties by optical microscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) and differential scanning calorimetry (DSC), respectively. The prepared samples contained only c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As for the glass‐ceramic sample treated before the crystallization peak, that is, at temperatures of 970 and 990°C, the presence of low‐intensity diffraction peaks was observed, corresponding to the beginning of the tetragonal gehlenite phase crystallization (2CaO.Al 2 O 3 .2SiO 2 or Ca 2 Al 2 SiO 7 ) (JPCDF 2–823). Majerová et al 16 . used high‐temperature XRD and showed that the gehlenite crystallization starts at 910°C, although low‐intensity peaks were observed from 800°C in their study.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…As for the glass‐ceramic sample treated before the crystallization peak, that is, at temperatures of 970 and 990°C, the presence of low‐intensity diffraction peaks was observed, corresponding to the beginning of the tetragonal gehlenite phase crystallization (2CaO.Al 2 O 3 .2SiO 2 or Ca 2 Al 2 SiO 7 ) (JPCDF 2–823). Majerová et al 16 . used high‐temperature XRD and showed that the gehlenite crystallization starts at 910°C, although low‐intensity peaks were observed from 800°C in their study.…”
Section: Resultsmentioning
confidence: 94%
“…14 In general, gehlenite has a hardness between 5 and 6 Mohs, which gives the material characteristics needed for various applications, such as its use as a constituent of ceramic construction materials, bio-soluble glass fibers, and glass ceramics. 16 There are studies in the literature that report on gehlenite production; however, few describe the production of glass ceramics containing this phase and obtained from the controlled crystallization of glass produced with biomass ash, as in our study. Li et al 7 prepared glasses from blast furnace slag varying the Al 2 O 3 :SiO 2 ratio, and they obtained glassceramics from the sintering of pellets produced with glass.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations